Investment Efficiency and Financial Performance: How Board Gender Diversity and Global Experience Make A Difference - Odeneska J.A. Purba; Syaiful Rahman Soenaria; Anies Lastiati (Green Publisher Indonesia, 2025)
The presence of women on the board of directors is believed to enhance the quality of investment decision-making through more diverse and risk-sensitive perspectives. These perspectives contribute to more effective investment management and have the potential to support improved corporate financial performance. Meanwhile, the CEO, as a strategic decision-maker, plays a crucial role in determining the company's investment direction, where the CEO's international exposure can broaden their insight in addressing global challenges. This study aims to analyze the influence of board gender diversity and CEO international exposure on investment efficiency and corporate financial performance. This research employs the Partial Least Square – Structural Equation Modelling (PLS-SEM) method with a sample of 154 manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2023. Secondary data were obtained from Refinitiv, the Indonesia Stock Exchange website, and annual reports. Control variables such as company size and operating cash flow were included to enhance the validity of the analysis results. The findings indicate that CEO gender does not affect either investment efficiency or financial performance. Conversely, CEO international exposure has a positive influence on investment efficiency and financial performance. Investment efficiency plays a significant role in improving financial performance and mediates the effect of CEO international exposure on financial performance. However, control variables company size have no effect, while operating cash flow positively impacts investment efficiency.